Author/Narrator in Late Antiquity: the case of Ammianus Marcellinus - Ivić, Nenad (2000)
This paper is divided in four parts: the first offers a critique of the usual ways of recostructing the authors biography from historical narrative based on maximistic discourse about human nature, authorship and scientific research; the second confronts the narrator and his multiform manifestations of orator, soldier and eye-witness with a previously described image; the third describes the invention/construction of the image of the stock-type historian and his communicational situation; the fourth points to narrative devices which create, for his public, the reality effect. Instead of narrative duplication of reality produced and narrated by an author, the late antique historical narrative revels itself as a complex text creating the historian and his history.
Projekt MZOS
ENG